Sensitive Fluorescent Sensor for Recognition of HIV-1 dsDNA by Using Glucose Oxidase and Triplex DNA - Yubin Li; Sheng Liu; Liansheng Ling (Journal of Analytical Methods in Chemistry)
A sensitive fluorescent sensor for sequence-specific recognition of double-stranded DNA (dsDNA) was developed on the surface of silver-coated glass slide (SCGS). Oligonucleotide-1 (Oligo-1) was designed to assemble on the surface of SCGS and act as capture DNA, and oligonucleotide-2 (Oligo-2) was designed as signal DNA. Upon addition of target HIV-1 dsDNA (Oligo-3•Oligo-4), signal DNA could bind on the surface of silver-coated glass because of the formation of C•GoC in parallel triplex DNA structure. Biotin-labeled glucose oxidase (biotin-GOx) could bind to signal DNA through the specific interaction of biotin-streptavidin, thereby GOx was attached to the surface of SCGS, which was dependent on the concentration of target HIV-1 dsDNA. GOx could catalyze the oxidation of glucose and yield H2O2, and the HPPA can be oxidized into a fluorescent product in the presence of HRP. Therefore, the concentration of target HIV-1 dsDNA could be estimated with fluorescence intensity. Under the optimum conditions, the fluorescence intensity was proportional to the concentration of target HIV-1 dsDNA over the range of 10 pM to 1000 pM, the detection limit was 3 pM. Moreover, the sensor had good sequence selectivity and practicability and might be applied for the diagnosis of HIV disease in the future.